Pengaruh Sistem Informasi SDM Terhadap Kinerja Karyawan Di PT. Rabbani Bandung - Jimmy Rusjiana (Jurnal Computech & Bisnis (e-Journal), 2016)
The purpose of this study was to determine the human resource information systems and employee performance in PT. Rabbani, and to determine how much influence human resource information systems to employees performance in PT. Rabbani. This research was conducted at PT Rabbani, to get the cause of the downward trend in employee performance. This allegedly caused by problems of human resource information systems, resulting in reduced performance of the employee. The method used is exploratory survey method using Equaltion stuctural Modeling SEM-PLS. Sample in the study were 36 employees. The results of this study indicate HR information system affect the performance of employees. Thus, the conclusions that can be drawn from this study that: to increase the influence of human resource information systems to employee performance, by following all the Standard Operating Company with regard phases that have been imposed by the company. Keywords: human resouces information system; performance.